Culture, biology, and anthropological demography - Roth, Eric Abella (Cambridge University Press, 2004)
Two distinctive approaches to the study of human demography exist within anthropology today: anthropological demography and human evolutionary ecology. The first stresses the role of culture in determining population parameters, while the second posits that demographic rates reflect adaptive behaviors that are the products of natural selection. Both sub-disciplines have achieved notable successes, but each has ignored and been actively disdainful of the other. This text attempts a rapprochement of anthropological demography and human evolutionary ecology through recognition of common research topics and the construction of a broad theoretical framework incorporating both cultural and biological motivation. Both these approaches are utilized to search for demographic strategies in varied cultural and temporal contexts ranging from African pastoralists through North American post-industrial societies. As such this book is relevant to cultural and biological anthropologists, demographers, sociologists, and historians
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Demographic anthropology; Human ecology; Human behavior; Mate selection; Social ecology; Humanökologie; Demographie